2d Game-Based Awareness Of Child Abduction For Public : Found You - Chua, Celin Wan Jin (2023)
The circumstances of child abduction and trafficking cases are serious and the public attention is low. In the United States, Britain, Australia, Spain and other countries, hundreds of thousands of minors and adults go missing every year. Although child trafficking is not as severe in Malaysia as in other countries, there are still hundreds of cases in Malaysia every year. Therefore a 2D game-based awareness of child abduction titled Found You has been published. Found You game able to allow players learn how to avoid from being kidnapped, learn the techniques will be used by a kidnapper when they try to kidnap, and increase the awareness and knowledge about the child abduction in players and public. The objectives of the project is to study the existing child abduction game application, design and develop a 2D child abduction awareness game application, and evaluate the functionality of the developed game application. During the analyzation on existing game application, it can be found that the 2D game application about child abduction is less. This project will be implement using Spiral Model with 4 phase which are Planning and Design, Implement, Playtest, and Evaluate. A Usability Acceptance Test (UAT) and Functional Acceptance Test (FAT) form is created and tested by 15 testers to ensure the game application is satisfied with tester expectation, the game is meet the objectives, and it is function well. From the FAT form all the results are 100% which means all the functions in the project are worked as expectation. For the UAT form, 13 out of 15 testers (86.7%) agree that the project is interesting and easy to understand. All the 15 testers are agree that the project is able to teach player about the techniques of protect themselves from being kidnapped and know the techniques or treats that will be used by kidnappers. Besides, 14 out of 15 testers (93.3%) agree that the project is able to increase the awareness of child abduction in player.